PHYLOGENY MAGNITUDE OF Mycobacterium tuberculosis BASED ON GENOMIC ANALYSIS - Budi Yanti; Mulyadi Mulyadi; Soetjipto Soetjipto; Ni Made Mertaniasih; Muhammad Amin (Faculty of Medicine, Universitas Islam Indonesia, 2020)
Mycobacterium tuberculosis (MTB) is mostly found in humans, and it can cause more than two million deaths each year with increasing morbidity. Although lineages of MTB show identical nucleotide relationships, they have different characteristics such as evolution, transmission, drug resistance, host interaction, latency, and vaccine effectiveness. It is necessary to have better understanding of MTB relationships based on similarities in genome sizes and phylogenetic analysis. This paper observes the relationships of MTB based on nucleotide through phylogenetic frameworks. The MTB species consist of six lineages, and each lineage has various size of genomes . This difference contributes to virulence of MTB affecting levels of severity, morbidity, and mortality of diseases. Genetic diversity of MTB can contribute to global threats in the world such as outbreak of tuberculosis, Multi Drug Resistant (MDR) and Extensively Drug Resistant (XDR) tuberculosis.